Study Pembuatan dan Karakterisasi Paduan Ingat Bentuk CuAlZn - Stefanus Andika Debby Purwanto; Budiarto; Bantu Hotsan Manullang; Syurkarni Ali; Din Aswan A Ritonga; Julian (Universitas Medan Area, 2023)
A study on the preparation and characterization of CuAlZn shape-remembering alloys has been carried out. The objective of the study was to determine the effect of mass variation of Cu and Zn on crystal structure, hardness and tensile strength of CuAlZn shape-remembering alloys with powder metallurgy. Sintering at 900°C for 90 minutes, then cooled rapidly with air. The results of the tests performed show that mass variations in Cu and Zn metals can affect the hardness and tensile strength values of the alloy. The greater the mass of Cu metal and the smaller the mass of Zn metal, the higher the hardness and tensile strength values of the CuAlZn alloy remember the shape.The results of the test performed showed that variations in metal mass in Cu and Zn metal could affect the hardness and tensile strength values of the alloy. The greater the mass of Cu metal and the smaller the mass of Zn metal, will produce a higher value of hardness and tensile strength of Shape Memory Alloy.